2011
DOI: 10.1016/s0917-2394(11)70222-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of congenitally missing permanent teeth in Japanese children: A survey conducted in south-west area of Kanto district

Abstract: AIM: The purpose of this study was to investigate the prevalence of congenitally missing permanent teeth in Japanese children residing in south-west area of Kanto district in recent years. METHODS: Panoramic radiographs taken for dental treatment between 1990 and 2007 were used to evaluate the congenitally missing permanent teeth excluding the third molar. The participants of this study consisted of 2,125 children aged between 7 and 20 years. RESULTS: The congenitally missing teeth were observed in 251 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
(38 reference statements)
2
10
1
Order By: Relevance
“…Previous studies on hypodontia have been equivocal regarding the influence of gender on prevalence. While most studies corroborate the results of this study stating no gender differences in hypodontia prevalence, other studies have shown a significantly greater prevalence of hypodontia in females . Many previous studies support the results of this study, stating no significant gender difference in the prevalence of peg‐shaped upper lateral incisors, impacted teeth, dental transpositions and double teeth …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous studies on hypodontia have been equivocal regarding the influence of gender on prevalence. While most studies corroborate the results of this study stating no gender differences in hypodontia prevalence, other studies have shown a significantly greater prevalence of hypodontia in females . Many previous studies support the results of this study, stating no significant gender difference in the prevalence of peg‐shaped upper lateral incisors, impacted teeth, dental transpositions and double teeth …”
Section: Discussionsupporting
confidence: 88%
“…Dental anomalies were identified according to the following definitions: Hyperdontia: Presence of 1 or more teeth or odontomes in addition to the regular number of permanent teeth . Diagnosed radiographically, or with evidence that a supernumerary tooth had been removed before, with sufficient details of the supernumerary tooth. Hypodontia: Developmental absence of 1 or more permanent teeth (excluding third molars) . Diagnosed radiographically with no recognized mineralization of the tooth crown, and no evidence that it had been removed before. Peg‐shaped upper lateral incisor: Undersized, tapered maxillary permanent lateral incisor which may be conical, have reduction in diameter from cervix to incisal edge, or with marked asymmetry in volume between right and left sides .…”
Section: Methodsmentioning
confidence: 99%
“…In this study, there was no gender difference in the prevalence of hypodontia for all subjects with CL/P and for the four groups: CL, CLA, CLP, and CP (Table 1). This issue has also been discussed for the subjects without CL/P (Brook, 1984;Suzuki et al, 1997;Polder et al, 2004;Pinho et al, 2005;Ide et al, 2011).…”
Section: Hypodontiamentioning
confidence: 97%
“…One meta-analysis has shown that tooth agenesis in Caucasian patients most commonly affects the mandibular second premolar (41.0%), followed by the maxillary lateral incisors (22.9%), and the maxillary second premolar (21.2%) 15) . Agenesis of the maxillary lateral incisor was reported to have the fourth highest incidence 5) and bilateral agenesis to most commonly affect the Japanese 17) . The mean width of the maxillary lateral incisor has been reported to be 7.07±0.43 mm, and be smallest in the maxilla 13) .…”
Section: Discussionmentioning
confidence: 99%
“…Dental agenesis is responsible for between 2% and 10% of missing teeth 7) . In Japanese people, the incidence of agenesis is highest for the mandibular second premolar, followed by the mandibular lateral incisors, the maxillary second premolar, and the maxillary lateral incisors 5) , and bilateral agenesis most commonly affects the maxillary lateral incisors 17) . Dental treatment aimed at rectifying functional disorder and esthetic disturbance due to agenesis of the maxillary lateral incisors involves orthodontic and/or prosthetic treatment, and will include a conventional bridge, a removable partial denture, and a dental implant 10) .…”
Section: Introductionmentioning
confidence: 99%